Keterlibatan Ayah dalam Intervensi Dini untuk Mengatasi Speech Delay pada Anak: Keterlibatan Ayah dalam Intervensi Dini untuk Mengatasi Speech Delay pada Anak - Muhammad Zulkarnaen; Noor Baiti (ITScience (Information Technology and Science), 2025)
Speech delay is a common developmental issue in early childhood that impacts communication skills, social interactions, and academic readiness. Early intervention is a crucial step in addressing this delay, but its effectiveness is greatly influenced by parental involvement, including fathers. This study aims to describe the role of fathers in early intervention to support the language development of children with speech delays. The study used a qualitative case study approach with several fathers of children with speech delays. Data were collected through in-depth interviews, observations, and documentation. The results showed that fathers' active involvement significantly impacted children's language development. Fathers who consistently provided stimulation such as reading stories, engaging in dialogue, playing while communicating, and responding to each child's verbal attempts accelerated the development of both expressive and receptive language. A father's more varied and exploratory communication style has been shown to enrich children's vocabulary, improve their ability to understand instructions, and encourage children to speak up. Furthermore, fathers' emotional support helps increase children's self-confidence and emotional regulation, making them better prepared to interact with their social environment. Research confirms that fathers' roles not only influence language development but also support children's cognitive and socio-emotional development. Thus, father involvement in early intervention is an important factor that must be strengthened to help children overcome speech delays and achieve optimal development.